Effective use of 2-termsets by discarding redundant member terms in bag-of-words representation - Badawi, Dima; Altincay, Hakan (Springer London Ltd, 2019)
Recent studies have proven the potential of using termsets to enrich the conventionally used bag-of-words-based representation of electronic documents by forming composite feature vectors. In this approach, some of the member terms may become redundant due to being strongly correlated with the corresponding termsets. On the other hand, the co-occurrence of terms may be more informative than their individual appearance. In these cases, removal of the member terms should be addressed to avoid the curse of dimensionality during model generation. In this study, elimination of member terms that become redundant due to employing 2-termsets is firstly addressed and two novel algorithms are developed for this purpose. The proposed algorithms are based on evaluating the relative discriminative powers and correlations of member terms and corresponding 2-termsets. As a third approach, evaluating redundancies of all terms when 2-termsets are used and discarding the terms that are most correlated with the 2-termsets is addressed. Simulations conducted on five benchmark datasets have verified the importance of eliminating redundant terms and effectiveness of the proposed algorithms.
Keywords: Termsets; Redundancy; Term selection; Document representation; Text classification